X) (X Sustituyanos: 2x2 Que X x2
X) (X Sustituyanos: 2x2 Que X x2
X) (X Sustituyanos: 2x2 Que X x2
10
·
X -
2x2
1
x2
=' x1
ya que pasa por
el (0 , 0)
-
2x , + x = 4 .
Si x, = C Si Xz = 0
8 + x2 = 4
1 -
2x + 0 = 4
x =
10
, 41 -
2x= 4
x = -2
( - 2
, 0)
3x , + 3x2 = IS sx, + 3x2 = IS
0 + 3x = 1 5x, + 0 = 1)
x2 = 15/3 x ,
=
(5/5
S x = 3
x =
,
10
.
3) 13 , 06
8z = (2 -
,
1) Para Su =
4 (X , + 2) +IR2 / 2 x, -
12 = K
Si K= 0 Si K = -
2x -
x = 0 2x -
x2 =
-
X2 = 2x1 -
+2 = - 2x , - 2
= 2x +2
x2
Sik 4 1 soluciona sã
z*
-
=
=> =
-
sus
-
-
2x-xy =
-
x2 =
-
2x1 - X
+ 4
& 3/x4 + 0(0 -
x)(X + (0 ,
-])
2x
xz
-
= .
sustituyanos Ae
5x , + 3x2 = /S X
H
2x - xy =
-
4 +
6x -
3x =
-
1
1x , -
=
3
2(3/1) -
k2 = -
4
#3/1 4 X = 4
-
-
A
A
-
>
-
+ 2 =
-
44/1 -
%1)
x2 = 50/1